Voice User Interface Projects: Build Voice-Enabled Applications Using Dialogflow for Google Home and Alexa Skills Kit for Amazon Echo - Lee, Henry (Packt Publishing, Limited, 2018)
The future of user interfaces is moving away from touch based and mouse clicking web interfaces to voice and conversational based user interfaces. This book will take you on a journey from getting started with voice apps to building your very own smart assistants which not only understand voice commands but respond to them.